Reaching 780,00 beneficiaries with CSA technologies in West Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Large projects aiming to increase communities resilience in WA are now taking action to scale up CSA technologies and practices to benefit their end-users. This came from technical support (advices and trainings) to capacitate the project actors (DryDev and SmAT-Scaling) based ground evidences that ICRAF developed in the framework of its pilot action research in BRAS-PAR (but also CASCAID). This allowed them to potentially reach 780,000 farmers with CSA options in WA.